Improving the performance of enterprise resource planning with the implementation of Systems, Applications, and Products in Data Processing (SAP) in a car seat manufacturing company - Widya, Adi Rusdi; Supriyati, Supriyati (Operations Excellence: Journal of Applied Industrial Engineering, 2024)
Using an Enterprise Resource Planning System (ERP) during the Industrial Revolution 4.0 is a long-term investment for companies looking to enhance efficiency, performance, productivity, and decision-making capabilities. Typically, ERP systems employ a centralized database to streamline various business processes, reducing manual labor and improving workflows. These systems often include a Dashboard that provides real-time data for measuring productivity and profitability. Updated instantly when entered into the system, this information allows companies to make quick, informed decisions based on accurate, up-to-date internal data. However, discrepancies between transaction processes, such as mismatches in the quantity of goods recorded in the SAP system and actual production, can hamper the effectiveness of ERP control. To address this, research has been carried out to process information in real time and with greater accuracy. The study involves a literature review, hardware prototypes, and program development, ultimately leading to increased SAP user accuracy from 63% to 86%. This improved accuracy helps identify factors hindering optimal SAP performance and provides recommendations for resolving transactional issues. Ultimately, consistency and commitment from users and relevant stakeholders are vital for maintaining an optimally functioning ERP system.